The Management Strategies of Serambi Mekkah Boarding School Meulaboh-West Aceh in Producing Well Behaved Students - Ummi Habibatul Islamiyah (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2019)
Islamic boarding schools (pesantren) as an informal institution has developed quite rapidly since the independence of the Republic of Indonesia. These developments are not only on the physical side such as infrastructure development & facility addition but also in terms of the management system that is implemented. Along with the times, the inclusion of formal education institutions into the pesantren education system and the increasing number of students have made the pesantren management face new challenges greater than ever before in producing well-behaved students. Any strategy adopted by the pesantren management to solve the problem, it will have a direct impact on the quality of students and alumnus. Therefore without the right approach, the purpose of pesantren to producing well-behaved students will not be realized. This study was conducted to determine the managements strategies of Serambi Mekkah Boarding School Meulaboh-West Aceh in producing well-behaved students. This research is a field study. Data obtained from interviews, documents and direct observation to the Serambi Mekkah Boarding School. Data were analyzed using ATLAS.ti software which facilitates researchers in organizing data, and presents it in a visual form. The results of this study found that the strategy applied to produce well-behaved students is by providing role models (uswah), using practice & habituation methods, discipline, giving motivation & advice regularly, and giving reward & punishment. Hopefully, this research can enrich insight and can be used as a reference by educational institutions in producing well-behaved students. DOI: https://doi.org/10.5281/zenodo.3467635